Prevalensi parasit Trichodina sp pada usaha budidaya ikan Nila (Oreochromis niloticus) di Pahandut Seberang Kota Palangka Raya. - Nyata Susila (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
This research was conducted to find out the prevalence of parasites Trichodina sp that infected tilapia (Oreochromis niloticus) from cages aquaculture at Village Pahandut Seberang, Palangka Raya City. A total of 60 sampled of tilapia are taken randomly from each cage and observed at Veterinary Laboratory of Palangka Raya to identified parasite Trichodina sp. Examination and identification of parasites is done natively by using a microscope. The results showed that parasite Trichodina sp found in 21 samples so that the prevalence of parasites Trichodina sp is 35%. Key words : Oreochromis niloticus, tilapia, prevalence, Trichodina sp.